Liturgi dan Keutuhan Ciptaan - Stenly Vianny Pondaag (Media (Jurnal Filsafat dan Teologi), 2020)
The essay deals with the relationship between liturgy und integrity of creation. It aims at providing a liturgical and theological explanation to the question: whether the Christian liturgy can contribute to the global movement regarding the integrity of creation. This study analyses theologically some selected eucharistic prayer texts in which the praise of God the Creator and of his works of creation occur. This study shows us that the theme of creation was an integral part of ancient Christian eucharistic prayers, and it remains the important element of the eucharistic prayers in the new time. The introduction of the theme of creation into the new eucharistic prayers in Roman Missal 1970 was one of the visible fruits of the eucharistic prayer reform after the second Vatican council. On the one hand, it expresses the new awareness of the richness of ancient liturgical tradition. On the other hand, the motif of creation has a close relevance to the hope and concern of our times. It should offer us a theological and liturgical inspiration in developing an ethical awareness and human responsibility toward the integration of creation.